"Nominata la patata... spuntato il purè" : lexical and phraseological puns in Disney handbooks - Benedetto Giuseppe Russo (Études romanes de Brno)
The paper sheds light on the language-stylistic reasons for the success of the Disney children's handbooks published by Mondadori, starting with the Manuale delle Giovani Marmotte (1969), containing curiosities, information on various subjects, tips, suggested pastimes and experiments. The appreciation it received led the same publisher to publish other volumes based on Disney's imagery, also destined for great popularity, including the Manuale di Nonna Papera (1970), a book of recipes introduced by historical anecdotes, and the Manuale del Gran Mogol (1980), also rich in multi-thematic notions, instructions and suggestions. Assuming that the success of Disney guidebooks was not only due to their practical and recreational usefulness, but to a large extent also to engaging communicative strategies, the forms of amusing language manipulation that made the three indicated volumes, the most famous ones, appealing to the very young generations of the second half of the 20th century are examined with relevant examples, i.e. the ways in which the creative and witty style of the authors is declined: puns, witty word juxtapositions, allusive paronomasias, reformulations of idioms and proverbs. The aim is to show how the effectiveness of a language for children that aims at being educational and also inspiring communicative creativity can strongly depend on strategically playful and therefore affable and compelling tones.